2016
DOI: 10.1016/j.adolescence.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of adolescents with currently and formerly incarcerated parents

Abstract: Reliable information about children of incarcerated people is difficult to obtain, and major gaps exist in our understanding of their well-being. This study aims to determine whether adolescents with incarcerated parents report higher levels of mental health problems than those without an incarcerated parent, and whether the relationship between parental incarceration and adolescent mental health is moderated by parent-child relationships. Using a statewide survey from one US state, we compared adolescents wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 109 publications
1
67
2
3
Order By: Relevance
“…For instance, a recent study found a higher risk of suicidal considerations and behavioral problems in youth (ages 12-19) who had a parent currently incarcerated or previously incarcerated compared to unexposed peers controlling for only two measures of socioeconomic disadvantage (e.g. family structure and poverty) (Davis & Shlafer, 2017). Others found a positive association between lifetime exposure to PI on attention, depression, anxiety, and conduct problems in children (0-18) controlling for five types of childhood adversity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a recent study found a higher risk of suicidal considerations and behavioral problems in youth (ages 12-19) who had a parent currently incarcerated or previously incarcerated compared to unexposed peers controlling for only two measures of socioeconomic disadvantage (e.g. family structure and poverty) (Davis & Shlafer, 2017). Others found a positive association between lifetime exposure to PI on attention, depression, anxiety, and conduct problems in children (0-18) controlling for five types of childhood adversity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In California, the state with the highest concentration of Hispanics (Pew Research Center, ), Hispanics have approximately twice the incarceration rate of non‐Hispanic whites and Hispanic children are 2.5 times as likely to have a family member in prison than non‐Hispanic White children (Public Policy Institute of California, ; The Sentencing Project, ). Research into the effects of incarceration on mental health outcomes suggests that, compared to their peers, children of incarcerated parents can have elevated symptoms of emotional problems and post‐traumatic stress disorder (Kampfner, ; Wilderman, ) and higher odds of suicidal ideation and suicide attempt (Bridge, Goldstein, & Brent, ; Davis & Shlafer, ), even after controlling for depression and gender (Mazza, ). Given that research investigating Hispanic young adult SI and SA is still limited, assessing whether familial incarceration has enduring effects on mental health and what factors could potentially mitigate the negative consequences of familial incarceration is an important area of study that has been challenged by the limited availability of longitudinal data from nonclinical, Hispanic community samples (King & Merchant, ).…”
Section: Introductionmentioning
confidence: 99%
“…Children of imprisoned mothers are predisposed to greater risks of maladjustment (8)(9) . Therefore, American, British and Australian institutions have sought, through programs, to strengthen family ties, recognizing the special needs of mothers and children.…”
Section: One Of the Guiding Principles Of The Brazilian National Polimentioning
confidence: 99%